Prevalence and progression of chronic kidney disease among adults undergoing creatinine testing in South African public healthcare facilities: a study leveraging data from South Africa's National Health Laboratory Service (NHLS) - Koleka Mlisana; Frederick Raal; Jacob Bor; Sydney Rosen; Nigel J Crowther; Kamy Chetty; Matthew P Fox; Patricia Hibberd; Alana T Brennan; Jaya A George; Emma M Kileel; Siyabonga Khoza (BMJ Publishing Group, 2024)
Background Chronic kidney disease (CKD) has emerged as a substantial global health challenge, with a marked rise in associated mortality. However, it often goes undetected until advanced stages, particularly in low-income and middle-income countries such as South Africa. We investigated the prevalence and progression of CKD in South Africa, utilising a subset of data from the National Health Laboratory Services Multi-morbidity Cohort.Methods This study was a retrospective analysis of adults aged 18-85 years who underwent initial creatinine laboratory testing at government hospitals and clinics from January 2012 to January 2016. CKD was assessed using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, excluding the race factor, with a cut-off of CKD-EPI<60 mL/min/1.73 m2. Lab-diagnosed CKD was defined as two estimated glomerular filtration rate measurements <60 mL/min/1.73 m2 at least 90 days apart. Cox regression and survival curves were used to estimate HRs and rates of progression.Results Among 6 106 521 adults tested between 2012 and 2016, 1.5% (95% CI 1.4% to 1.5%) were diagnosed with CKD, with the majority in stage 3. Over follow-up (median: 2 years, IQR: 0.8-3.6 years), 28.2% (95% CI 27.7% to 28.6%) of patients diagnosed as stage 3a progressed to a more severe disease state. Among patients who were in stage 3b at diagnosis, 29.6% (95% CI 29.0% to 30.1%) progressed and 33.3% (95% CI 32.5% to 34.1%) of stage 4 patients progressed. We estimated a 48% higher adjusted hazard of CKD progression for individuals with diabetes (adjusted HR 1.48, 95% CI 1.41 to 1.57) compared with those without. Advancing age also increased the risk, particularly for those aged >50 years.Conclusions This study underscores the urgency for early detection and management of CKD in South Africa, particularly for high-risk individuals. Strengthening primary healthcare systems and raising CKD awareness are vital for improved patient outcomes and to alleviate the burden on healthcare resources. Early intervention can delay CKD progression, thus reducing the need for costly treatments like dialysis and transplantation.